The Societalization of Social Problems: Church Pedophilia, Phone Hacking, and the Financial Crisis - Alexander, Jeffrey C. (American sociological review, 2018)
This article develops a theory of “societalization,” demonstrating its plausibility through empirical analyses of church pedophilia, media phone-hacking, and the financial crisis. Although these strains were endemic for decades, they had failed to generate broad crises. Reactions were confined inside institutional boundaries and handled by intra-institutional elites according to the cultural logics of their particular spheres. The theory proposes that boundaries between spheres can be breached only if there is code switching. When strains become subject to the cultural logics of the civil sphere, widespread anguish emerges about social justice and concern for the future of democratic society. Once admired institutional elites come to be depicted as perpetrators, and the civil sphere becomes intrusive legally and organizationally, leading to repairs that aim for civil purification. Institutional elites soon engage in backlash efforts to resist reform, and a war of the spheres ensues. After developing this macro-institutional model, I conceptualize civil sphere agents, the journalists and legal investigators upon whose successful performances the actual unfolding of societalization depends. I also explore “limit conditions,” the structures that block societalization. I conclude by examining societalization, not in society but in social theory, contrasting the model with social constructionism, on the one hand, and broad traditions of macro-sociological theory, on the other.